Evolutionary characterization of pig interferon-inducible transmembrane gene family and member expression dynamics in tracheobronchial lymph nodes of pigs infected with swine respiratory disease viruses - Miller, Laura C.; Jiang, Zhihua; Sang, Yongming; Harhay, Gregory P.; Lager, Kelly M. (My University, 2014)
Studies have found that a cluster of duplicated gene loci encoding the interferon-inducible transmembrane proteins (IFITMs) family have antiviral activity against several viruses, including influenza A virus. The gene family has 5 and 7 members in humans and mice, respectively. Here, we confirm the current annotation of pig IFITM1, IFITM2, IFITM3, IFITM5, IFITM1L1 and IFITM1L4, manually annotated IFITM1L2, IFITM1L3, IFITM5L, IFITM3L1 and IFITM3L2, and provide expressed sequence tag (EST) and/or mRNA evidence, not contained with the NCBI Reference Sequence database (RefSeq), for the existence of IFITM6, IFITM7 and a new IFITM1-like (IFITM1LN) gene in pigs. Phylogenic analyses showed seven porcine IFITM genes with highly conserved human/mouse orthologs known to have anti-viral activity. Digital Gene Expression Tag Profiling (DGETP) of swine tracheobronchial lymph nodes (TBLN) of pigs infected with swine influenza virus (SIV), porcine pseudorabies virus, porcine reproductive and respiratory syndrome virus or porcine circovirus type 2 over 14 days post-inoculation (dpi) showed that gene expression abundance differs dramatically among pig IFITM family members, ranging from 0 to over 3,000 tags per million. In particular, SIV upregulated IFITM1 by 5.9 fold at 3 dpi. Bayesian framework further identified pig IFITM1 and IFITM3 as differentially expressed genes in the overall transcriptome analysis. In addition to being a component of protein complexes involved in homotypic adhesion, the IFITM1 is also associated with pathways related to regulation of cell proliferation and IFITM3 is involved in immune responses.
Keywords: Interferon-inducible transmembrane protein family member; IFITM; Swine genome; Influenza virus